Study on the mobile phase composition and flow rate parameter for tributyrin using high performance liquid chromatography-uv detector (HPLC-UV) / Fariswan Atan - Atan, Fariswan (2019)
The chromatographic separation for standard tributyrin was done by using high performance liquid chromatography (HPLC) equipped with ultraviolet (UV) detector. 20 µL of tributyrin standard with concentration of 0.018 rnM was injected into HPLC attached to the column Carbonl8 (Cl8) at 215 nm wavelength. Two optimization of HPLC parameters have been done in order to study the best condition for tributyrin elution. Two parameters were studied for the elution of tributyrin which are mobile phase composition and flowrate. It was found that the optimum mobile phase composition for tributyin was 50:50 acetonitrile:acetone and the optimum flowrate for tributyrin was at 0.55 mL/min. The calibration curve of standard tributyrin's range was found proportionally linear to tributyrin concentration from 0.009-0.075 mM and the value of R2 was 0.9502. Limit of detection (LOD) and limit of quantitation (LOQ) also have been conducted in this study. The value of LOD and LOQ obtained from the calculation were 0.0032 rnM and 0.0096 mM respectively.